Environmental and human-health risks of As in soils with abnormal arsenic levels located in irrigated agricultural areas of Paracatu (MG), Brazil - Feitosa, Marina Monteiro; Alvarenga, Ingrid Fernanda Santana; Jara, Madeliny Saracho; Lima, Geraldo Jânio Eugênio de Oliveira; Vilela, Fernando José; Resende, Thiago; Guilherme, Luiz Roberto Guimarães (Ecotoxicology and environmental safety, 2021)
The municipality of Paracatu (Brazil) is notorious for its large irrigated agricultural area and by abnormal arsenic (As) levels in selected soils of the region. Concerns regarding As exposure via ingestion of water and food are frequent, yet little is known about the behavior of arsenic in irrigated agricultural soils, as well as on As bioaccessibility/bioavailability in agroecosystems of this region. This work evaluated total and available As in agricultural soils cultivated under irrigation and in soils under native vegetation in Paracatu. We also assessed reactive arsenic fractions and As bioaccessibility in the soil, as well as arsenic levels in plant shoots to estimate As risks in these agroecosystems. Soil (different depths) and plant tissue samples were collected in 6 irrigated agricultural areas (CA1 to CA6) and 4 reference areas (RA1 to RA4). Total soil-As did not differ between soil depths, reinforcing that the source of As in agricultural soils is natural. This was evident when counterpointing arsenic and phosphorus contents at different soil depths, as both accumulate on the surface of oxidic soils when added to agroecosystems by anthropogenic routes (e.g., phosphate fertilization for P and irrigation for As). Available As levels in soils and plants were very small (below detection limit). Furthermore, all soils presented very low oral As bioaccessibility. Our findings revealed that the irrigated soils are not As polluted due to the low enrichment and accumulation of arsenic, as well as the prevalence of low ecological risks. There is no non-carcinogenic risk for the local population, except for children in RA2. The estimated carcinogenic risk for children followed the order RA2 > CA3 > CA4 > RA3 > CA2, and for adults, RA2 > CA3. Ultimately, the strategy of comparing the behavior of P and As in the soils of this study proved to be efficient in showing that there are no major risks to humans and the environment in the investigated area. However, periodic monitoring of As bioavailability in these areas is recommended. [Display omitted] •Irrigation water is not a relevant source of As in agricultural soils of Paracatu.•High As contents in agricultural soils are of geogenic origin.•As is not bioavailable for plants, ensuring food safety.•All evaluated soils had very low As oral bioaccessibility.•Cultivated areas present low to moderate ecological risk.